Capillary electrochromatography of inorganic and small organic anions using pseudo and wall-coated ion exchange phases - Breadmore, MC (2001)
This work presents a systematic study on the use of pseudo-phase and wall-coated ion-exchange (IE) phases for the separation of anions by ion-exchange capillary electrochromatography (IE-CEC). The viability of using open tubular (OT) columns prepared by adsorbing small cationic particles onto the capillary wall for the selectivity manipulation of inorganic anions by IE-CEC was examined. The introduction of an IE component into the separation mechanism allowed the separation selectivity to be varied by changing the type and concentration of the electrolyte anion. This enabled the migration order of a mixture of ions to be changed from a chromatographic selectivity to an electrophoretic selectivity, via novel intermediate selectivities. When separating UV transparent ions, the IE competing ion also acted as the indirect detection probe, which restricted the range over which the concentration could be varied. Selectivity manipulation in this case was achieved by varying the type of probe rather than its concentration. Using a theoretical model equation derived from IC and CE theory, the manner in which mobilities changed with varying electrolyte composition was modelled, with excellent correlation being obtained between predicted and experimental analyte mobilities (r2> 0.98). Values for analyte constants determined from non-linear regression allowed a quantitative comparison of the strengths of interaction of different ions with the ion-exchange phase. The addition of the cationic polymer, poly(diallyldimethylammonium chloride), to the electrolyte as an alternative to OT columns provided superior flexibility due to the ability to vary the IE capacity. The model derived for the migration of anions in the OT system was extended to include the ability to vary the IE capacity and was validated with a test set of 16 UV absorbing inorganic and organic anions. Excellent agreement (r2> 0.98) was obtained between experimental and predicted mobilities for all ions. The model was used to find the optimum separation conditions, with the separation of 16 ions being achieved on the basis of only 5 initial experiments. The system was then extended to the analysis of UV transparent ions where the separation of 24 anions was optimised using the derived model equation. The potential of using pseudo-phase IE-CEC for the separation of real samples was demonstrated with the separation of anions in Bayer liquor. The advantage of having a heterogeneous phase in an OT column was exploited to enable the on-capillary preconcentration of inorganic anions via IE interactions. A new elution method, namely the use of a transient isotachophoretic gradient, was introduced and shown to be a very efficient method for analyte elution from the preconcentration column. A fundamental study of the generation and implementation of the gradient was undertaken and the optimum conditions enabled nearly a 1000-fold increase in sensitivity over conventional CE without the use of electrokinetic injection. The potential of the method was demonstrated by the determination of nitrate in Antarctic ice cores.